2017
DOI: 10.1111/add.13855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 0.5 mg versus 1 mg varenicline for smoking cessation: a randomized controlled trial

Abstract: There appears to be no difference in smoking cessation effectiveness between 1 mg and 0.5 mg varenicline, both administered twice daily for 8 weeks, with similar rates of abstinence (46.5% versus 46.4%), adherence and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
10
0
3
Order By: Relevance
“…Most of the studies included in this review consisted of RCTs ( n = 38) [ 32 69 ], followed by cohort ( n = 17) [ 70 86 ], cross-sectional ( n = 3) [ 87 89 ], quasi-experimental ( n = 3) [ 90 92 ], and qualitative ( n = 1) [ 93 ] studies, and one study ( n = 1) [ 53 ] was a mediation analysis that examined an observational study and RCT. The majority of studies had a low to moderate risk of bias [27 studies were of low risk of bias [ 37 39 , 42 , 44 , 47 56 , 61 , 65 , 71 73 , 75 , 83 , 84 , 86 , 88 , 92 , 93 ]; 28 studies were of moderate risk [ 32 , 33 , 35 , 40 , 41 , 43 , 45 , 46 , 59 , 60 , 62 64 , 66 70 , 77 82 , 85 , 87 , 89 , 90 ]; and six studies were of high risk of bias [ 36 , 57 , 58 , 74 , 76 , 91 ]]. Studies were conducted in a multitude of countries across all continents except Antarctica.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies included in this review consisted of RCTs ( n = 38) [ 32 69 ], followed by cohort ( n = 17) [ 70 86 ], cross-sectional ( n = 3) [ 87 89 ], quasi-experimental ( n = 3) [ 90 92 ], and qualitative ( n = 1) [ 93 ] studies, and one study ( n = 1) [ 53 ] was a mediation analysis that examined an observational study and RCT. The majority of studies had a low to moderate risk of bias [27 studies were of low risk of bias [ 37 39 , 42 , 44 , 47 56 , 61 , 65 , 71 73 , 75 , 83 , 84 , 86 , 88 , 92 , 93 ]; 28 studies were of moderate risk [ 32 , 33 , 35 , 40 , 41 , 43 , 45 , 46 , 59 , 60 , 62 64 , 66 70 , 77 82 , 85 , 87 , 89 , 90 ]; and six studies were of high risk of bias [ 36 , 57 , 58 , 74 , 76 , 91 ]]. Studies were conducted in a multitude of countries across all continents except Antarctica.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included in this review reported barriers as opposed to facilitators. Of the 61 studies, 51 studies [ 32 , 33 , 36 40 , 42 57 , 59 65 , 67 69 , 71 , 73 78 , 80 83 , 86 92 ] only mentioned barriers, while four studies [ 41 , 58 , 66 , 85 ] only mentioned facilitators, and six studies mentioned both barriers and facilitators [ 35 , 37 , 70 , 79 , 84 , 93 ]. Definitions of the theoretical domains according to Atkins, et al [ 94 ] can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Также исключили работы с существенно измененной длительностью курса приема варениклина [23,26,33,38,39,41,52,74,78,100,106]. Исключены исследования, у которых отсутствовала контрольная группа [31]. Исключены работы, где фармакологическую терапию начинали после терапии НЗТ или использовали комбинацию препаратов [22,40,46,48,57,58,82,[87][88][89].…”
Section: Introductionunclassified